Most influential scholars in criminology and criminal justice, 1986-2020 - Cohn, Ellen G. (SpringerBriefs in Criminology, 2023)
This brief examines the influence and prestige of scholars and works in the field of criminology and criminal justice, as well as changes in influence and prestige over a period of 35 years, using citation analysis. Based on responses to prior research, most criminologists consider the results both fascinating and thought-provoking, although methods of measuring scholarly influence are also highly controversial. The brief includes 35 years of data (1986 through 2020) on the most-cited scholars and works in major American and international criminology and criminal justice journals, and provides an objective measure of scholarly influence and prestige. Appropriate for graduate students and researchers, it helps to document the intellectual development of criminology and criminal justice as a field of study.